Building a Regional Academic Integrity Network: Profiling the Growth and Action of the Academic Integrity Council of Ontario - McKenzie, Amanda; Miron, Jennie; Ridgley, Andrea (Canadian Perspectives on Academic Integrity, 2020)
Since 2008, the Academic Integrity Council of Ontario (AICO) has provided a forum for academic integrity practitioners and representatives from post-secondary institutions in Ontario to share information, and to facilitate the establishment and promotion of academic integrity best practices. This article is a summary of a presentation given at the Canadian Symposium on Academic Integrity, which was organized and held at the University of Calgary in April 2019. The creation, operation and role of the Council, and how it serves to connect post-secondary institutions in Ontario on academic integrity-related matters is described. This will include the benefits that such an association brings between institutions, and some of the accomplishments to date, like the establishment and ongoing work of a contract cheating sub-committee. The most recent achievement of mobilizing academic integrity practitioners at a national level is also described.